Los temas policiales y la violencia, los asuntos priorizados por el diario más exitoso de habla hispana - Villalobos León, María Gabriela (2020)
The Trome newspaper is considered both a commercial and journalistic success. It is the biggest selling Spanishlanguage daily, with the largest readership. The aim of this study was to identify the type of stories prioritized by Trome, and to establish the principal characteristics underlying its portrayal of everyday life. For this analysis, information related to the publication’s eighteen-year history was studied, together with twenty-one consecutive editions, while giving particular emphasis to their front page headlines, and those featuring in the paper’s most extensive sections, namely “Actualidad” (“Current Affairs”) and “Fiesta” (“Entertainment”). Our study determined that issues related to crime and violence predominate in the newspaper’s depiction of everyday life; in fact, 100% of the editions analyzed prioritized in the form of a front page headline a story related to a situation involving violence or conflict. At the same time, 76% of the content in those editions analyzed focused on crime-related stories, despite the fact that the newspaper does not contain a crime section.